Effect of Willow Tit Poecile montanus alarm calls on attack rates by Pygmy Owls Glaucidium passerinum. (16th March 2013) - Kareksela, Santtu; Härmä, Oskari; Lindstedt, Carita; Siitari, Heli; Suhonen, Jukka; Pichegru., Lorien
<x xml:space="preserve">Abstract</x> One suggested anti‐predator function of alarm calls is to deliver a message to a predator that it has been detected. Moreover, giving the alarm call could provide a signal to the predator that capturing the individual giving the alarm is more difficult than capturing its silent group members, as the caller is probably the most aware of the predator's location. In an aviary experiment using stuffed dummy Willow Tits Poecile montanus, we assessed whether an authentic alarm call given by Willow Tit affected Pygmy Owl Glaucidium passerinum prey preference. In the experiment, the Owls attacked only the 'silent' dummy individuals, suggesting that alarm calling could offer direct fitness benefits to the caller by decreasing the attack risk of the caller relative to its group members.